ANALISIS STRATEGI KEUNGGULAN BERSAING DENGAN PENDEKATAN PROSES JARINGAN KERJA KAJIAN EMPIRIS PADA BUMN PERKEBUNAN - Dendi Anggi Gumilang; Arief Daryanto; Bustanul Arifin; Rudi Wibowo (Jurnal Manajemen., 2014)
This research explores the strategy of change management to increase competitiveness of BUMN Perkebunan, especially in Tobacco business. The objectives of this research are: (1) to analyse internal factors of BUMN Perkebunan needed for increasing competitiveness in tobacco business, (2) to analyse policies needed for increasing competitiveness of BUMN Perkebunan in tobacco business, (3) to formulate strategy by PT ABC to increase competitiveness of BUMN Perkebunan in tobacco business. The data were taken from relevant literatures, indepth interviews, and expert panels. The research has shown that in the future, BUMN Perkebunan has to prioritize its role and function on the business aspect, enhanced by strong commitment from the government. On the other hand, resources and demand conditions are two aspects to be prioritized to increase PT ABC competitiveness. The alternative strategy to that end lies in the product development.